THE CORRELATION BETWEEN THE STUDENTS’ PERCEPTION ON THE LECTURERS’ ABILITY IN MAKING LESSON PLAN AND THEIR ACHIEVEMENT IN TEFL AT ENGLISH DEPARTMENT OF TARBIYAH FACULTY IAIN-SU - Afdhalina (Jurnal Scientia, 2020)
Prepare before teaching is very important acion, in order to make teaching easily. One of the prepare is making a lesson plan. Lesson plan is software for teacher to track the lessson plan for their classes. The goal of this research is to find out “The correlation between the students’ perception on the lecturer’s ability in making lesson plan and their achievement in TEFL at English Educational Department of Tarbiyah Faculty IAIN-SU”. The study was conducted on the nineth semester students of English Educational Department of Tarbiyah Faculty IAIN SU Medan. The population of this study was 78 and the writer took all population as a sample. The data was analyzed by the Product Moment Correlation technique. From the calculation of the data, it found that there is a significant correlation between the students’ perception on the lecturers’ ability in making lesson plan and their achievement in TEFL or the Hypothesis Alternative (Ha) is accepted and the Null Hypothesis (Ho) is rejected. Because rcalculate is bigger than rtable or 0.336>0.224.